A Novel Nitronyl Nitroxide with Salicylic Acid Framework Attenuates Pain Hypersensitivity and Ectopic Neuronal Discharges in Radicular Low Back Pain. (1st November 2015) - Han, Wen-Juan; Chen, Lei; Wang, Hai-Bo; Liu, Xiang-Zeng; Hu, San-Jue; Sun, Xiao-Li; Luo, Ceng
Abstract : Evidence has accumulated that reactive oxygen species and inflammation play crucial roles in the development of chronic pain, including radicular low back pain. Nonsteroid anti-inflammatory drugs (NSAIDs), for example, salicylic acid, aspirin, provided analgesic effects in various types of pain. However, long-term use of these drugs causes unwanted side effects, which limits their implication. Stable nitronyl (NIT) nitroxide radicals have been extensively studied as a unique and interesting class of new antioxidants for protection against oxidative damage. The present study synthesized a novel NIT nitroxide radical with salicylic acid framework (SANR) to provide synergistic effect of both antioxidation and antiinflammation. We demonstrated for the first time that both acute and repeated SANR treatment exerted dramatic analgesic effect in radicular low back pain mimicked by chronic compression of dorsal root ganglion in rats. This analgesic potency was more potent than that produced by classical NSAIDs aspirin and traditional nitroxide radical Tempol alone. Furthermore, SANR-induced behavioral analgesia is found to be mediated, at least in partial, by a reduction of ectopic spontaneous discharges in injured DRG neurons. Therefore, the synthesized NIT nitroxide radical coupling with salicylic acid framework may represent a novel potential therapeutic candidate for treatment of chronic pain, including radicular low back pain.